Managing information overload in virtual teams: Effects of a structured online team adaptation on cognition and performance - Ellwart, Thomas; Happ, Christian; Gurtner, Andrea; Rack, Oliver (European journal of work and organizational psychology, 2015)
Information overload (IO) indicates the exchange of too much low-quality information in virtual teams. When being overloaded with information, teams need to adapt and to change communication behaviour. This study introduces and tests a structured online team adaptation (STROTA) procedure that enables virtual teams to reduce IO by improving their team mental model quality. STROTA, built from team adaptation models, is a moderated intervention consisting of three stages: (1) individual situation awareness, (2) team situation awareness, and (3) plan formulation. STROTA was tested in the context of an experimental problem-solving task. Participants (N = 363) worked in virtual teams of three and were randomly assigned to one of four experimental conditions: no STROTA, incomplete STROTA (step 1, steps 1-2), and complete STROTA (steps 1-2-3). We found teams that followed a complete STROTA procedure experienced lessened IO over time. Teams with complete STROTA showed the largest development of TMM immediately after STROTA. Finally, multilevel mediation analyses showed that TMM are mediators that explain the influence of STROTA on IO.